1979
DOI: 10.1111/1523-1747.ep12676385
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Induction and Clinical Occurrences of Combined Clindamycin and Erythromycin Resistance in Corynebacterium acnes

Abstract: Corynebacterium acnes strains cross-resistant to clindamycin and erythromycin were observed following long-term selection or mutagenic treatment in the laboratory. Similar strains were found among clinical isolates from patients using clindamycin or erythromycin topically in the treatment of acne vulgaris. Clindamycin resistance was never observed in the absence of resistance to macrolides or other lincosaminides. It is suggested that this resistance may result from an alteration of the 50S ribosomal subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
6

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 10 publications
0
40
0
6
Order By: Relevance
“…A number of unrelated factors that might contribute to failure of therapy have been considered, including antibiotic resistance in propionibacteria (Leyden, 1976;Cunliffe et al, 198 1) but because resistance was not commonly observed it seemed unlikely to be an important cause of treatment failure (Leyden, 1976). However, Crawford et al (1979) found a substantial incidence of resistance in propionibacteria isolated from patients on topical erythromycin or clindamycin after treatment for 8 weeks or longer; strains were resistant to both drugs. Phenotypically similar strains were derived from sensitive strains in vitro but the genetic basis of their resistance was not necessarily similar (Crawford et al, 1979).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A number of unrelated factors that might contribute to failure of therapy have been considered, including antibiotic resistance in propionibacteria (Leyden, 1976;Cunliffe et al, 198 1) but because resistance was not commonly observed it seemed unlikely to be an important cause of treatment failure (Leyden, 1976). However, Crawford et al (1979) found a substantial incidence of resistance in propionibacteria isolated from patients on topical erythromycin or clindamycin after treatment for 8 weeks or longer; strains were resistant to both drugs. Phenotypically similar strains were derived from sensitive strains in vitro but the genetic basis of their resistance was not necessarily similar (Crawford et al, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…However, Crawford et al (1979) found a substantial incidence of resistance in propionibacteria isolated from patients on topical erythromycin or clindamycin after treatment for 8 weeks or longer; strains were resistant to both drugs. Phenotypically similar strains were derived from sensitive strains in vitro but the genetic basis of their resistance was not necessarily similar (Crawford et al, 1979). The present results confirm that such strains can be isolated from patients on oral clindamycin therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the late 1970s, a few strains of P. acnes that were relatively insensitive to erythromycin and clindamycin were first reported and were not viewed to be clinically significant [1]. In the early 1980s, shortly after the introduction of topical formulations of erythromycin and clindamycin, clinically relevant, less-sensitive strains were reported from a small group of patients in the USA [2].…”
Section: Introductionmentioning
confidence: 99%
“…At the time, it had not been possible to experimentally induce propionibacterial resistance nor could clinically resistant strains be isolated. In 1979, however, Crawford et al [14]found combined erythromycin/clindamycin resistance in propionibacteria isolated from comedones in 2 of 143 patients who underwent long-term clindamycin therapy. Thereafter, numerous studies found an increase in propionibacterial resistances in both the USA and Europe.…”
Section: Introductionmentioning
confidence: 99%